The influence of maternal singing on well-being, postpartum depression and bonding - a randomised, controlled trial - Verena Wulff; Philip Hepp; Oliver T. Wolf; Tanja Fehm; Nora K. Schaal (BMC, 2021)
Abstract Background Postpartum depression is fairly common in new mothers and moreover associated with impaired bonding and poor maternal well-being. The aim of the present study was to investigate the impact of a mother-infant singing intervention within the first three months after birth on maternal well-being, depressive symptoms and bonding. Methods 120 women who were recruited at the maternity ward at the University Clinic in Düsseldorf took part in this prospective, randomised-controlled study. Beside the baseline measurement 1-3 days after childbirth, depressive symptoms, maternal well-being and mother-infant bonding were evaluated with questionnaires before (two weeks after birth) and after (twelve weeks after birth) the intervention took place. The experimental group (n = 59) participated in several singing intervention sessions while the control group (n = 61) did not. In the intervention group, salivary cortisol as well as attachment and mood were assessed immediately before and after the singing sessions. Results The participants of the intervention group showed a significant reduction of cortisol (p = .023) and an improvement of attachment and mood from start to end of the intervention session (all p ≤ .008). However, no prolonged effects were revealed beyond the intervention sessions as the two groups did not differ regarding the alterations of the primary outcomes postpartum depression (interaction effect p = .187) and postpartum bonding (interaction effect p = .188) in the 10-week period from two up to twelve weeks after childbirth (all p > .05). Additional analyses of singing habits at home in both groups, revealed that only in the singing group more frequent singing was associated with less anxiety and more well-being of the mother. Conclusion Singing towards the infant seems to have positive immediate effects on the well-being of new mothers (on subjective variables as well as physiological measurements). However, the intervention did not lead to more long lasting positive effects although several limitations should be considered. Trial registration DRKS00015178 (registered at the German Clinical Trial Registry), date of registration: 09.11.2018.